CYBER INSTITUTIONS IN HANDLING BANKING CRIMES IN INDONESIA - Putu Agung Putra Baharata; Putu Dima Indra (LPPM Universitas Ekasakti Padang, 2023)
The formulation in the context of overcoming cyber crimes in the banking sector, where the existence of the establishment of cyber institutions within the Indonesian Police is inseparable from the cases that have hit the banking world. Online-based loans do not only have a good impact on society, but also have negative effects, such as fraudulent persons. The mode of online loan-based fraud occurs in people who are in a state of economic problems or it could also be due to negligence because the lure of easy loans and very low interest. This problem can actually be overcome by triggering factors from the community to learn and participate in pursuing the development of existing technology.